Status Kewarisan Anak Hasil Perjanjian Surogasi Dalam Prespektif Hukum Islam - Reni Novita Anggriani Sitompul (Universitas Islam Madura, 2021)
In this era of globalization, the development of science and technology is increasingly felt. Not only in the field of telecommunications, but also in the field of medicine, the discovery of a new program in artificial insemination with a mother surrogate method or commonly called uterine rental. Surrogate mother is the practice of renting a woman who binds herself in an agreement with another party with the aim of being able to get pregnant and give birth to a baby whose sperm and ovum were previously combined with the other party's partner, the result of the compound being implanted in the woman's womb. This discovery raises new problems in the rules of Islamic law, related to the status of children born with this surrogacy agreement. The method used by the author in answering the above problems is library research and a juridical-normative approach. The data used in this study is secondary data obtained by literature study and then processed and analyzed. Based on the background, the researcher is interested in studying the inheritance status of the children resulting from the surrogacy agreement. The conclusion in this study, all fiqh experts do not allow the rental of wombs in various forms, because it will cause confusion in the inheritance status of children born from surrogacy agreements.